One little lie eaudiobook - Coble, Colleen (Pelican Harbor, 2020)
It started with one little lie. But Jane Hardy will do everything in her power to uncover the truth in this gripping romantic suspense from USA TODAY Bestselling author Colleen Coble. Jane Hardy is appointed interim sheriff in Pelican Harbor, Alabama, after her father retires, but there's no time for an adjustment period. When her father is arrested for theft and then implicated in a recent murder, Jane quickly realizes someone is attempting to destroy the only family she has. After escaping with her father from a cult fifteen years ago, Jane has searched relentlessly for her mother—who refused to leave—ever since. Could someone from that horrible past have found them? Reid Dixon is well-known for his documentaries, and his latest project involves covering Jane's career. Jane has little interest in the attention, but the committee who appointed her loves the idea of the publicity. Jane finds herself depending on Reid's calm manner as he follows her around filming, and they begin working together to clear her father. But Reid has his own secrets from the past, and the gulf between them may be impossible to cross—especially once her father's lie catches up with him. "There are just enough threads left dangling at the end of this well-crafted romantic suspense to leave fans hungrily awaiting the next installment." —Publishers Weekly | "Colleen Coble once again proves she is at the pinnacle of Christian romantic suspense. Filled with characters you'll come to love, faith lost and found, and scenes that will have you holding your breath . . ." —Lisa Wingate | "One Little Lie is One Phenomenal Read." —Lynette Eason Readers love these novels because of the strong, relatable characters, the fast-paced suspense, the layers of family drama, and the themes of redemption. The Pelican Harbor Series is best read in order and includes One Little Lie, Two Reasons to Run, and Three Missing Days. Each novel contains discussion questions perfect for book clubs. Looking for more from these characters? Find cameo appearances from them in the Tupelo Grove Series from Colleen Coble and Rick Acker (What We Hide, Where Secrets Lie, and When Justice Comes).